The Influence of Work Environment, Workload, and Career Development on Employee Performance - La’bi’, Melisa Liku; Zakaria, Zakaria; Mulyanti, Rita Yuni (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study investigates the impact of work environment, workload, and career development on employee performance at the Ministry of Religious Affairs in South Papua Province. The research aims to determine the significance of these variables on performance. Using a quantitative method, data were collected through structured questionnaires and analyzed using multiple regression. Results show that work environment and workload significantly affect performance, while career development does not. Simultaneously, all variables collectively impact performance. The findings suggest improving the work environment, managing workload effectively, and enhancing career development opportunities to boost employee performance. Future research should expand the sample size and include additional variables.